2013
DOI: 10.1111/cid.12027
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate Is CBCT in Measuring Bone Density? A Comparative CBCT‐CT In Vitro Study

Abstract: The lower radiation dose and reduced costs of CBCT make this a useful substitute for CT; however, this study has shown that, in order to more accurately define the bone density with CBCT, a conversion ratio needs to be applied to the VV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 14 publications
5
78
2
6
Order By: Relevance
“…Other studies have suggested an application of the conversion ratio to CT numbers in order to calculate the bone density using CBCT 16. Our data emphasize the complex influences of anatomic location, FOV, and different CBCT units on CT numbers.…”
Section: Discussionmentioning
confidence: 51%
“…Other studies have suggested an application of the conversion ratio to CT numbers in order to calculate the bone density using CBCT 16. Our data emphasize the complex influences of anatomic location, FOV, and different CBCT units on CT numbers.…”
Section: Discussionmentioning
confidence: 51%
“…According to their results, gray density of CBCT is higher than in CT. However, there is an excellent correlation between CT and CBCT (3). There are similar studies consistent with our findings, which demonstrated positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that conventional dental imaging procedures and systems have limited capability for preoperative planning and implant surgeries (2). The quality, quantity, and density of the jaw are important factors in implant treatment (3). Besides, mechanical characteristics are an important factor in Osseo integration and primary stability of the implant (48).…”
Section: Introductionmentioning
confidence: 99%
“…CBCT, 19,20 CT and panoramic radiography are traditionally used in oral and maxillofacial surgery; 21,22 during the post-operative period, these imaging methods can delineate deformity of the mandibular canal bone structure, but the morphologic changes of the IAN cannot be evaluated. Several studies demonstrated that MRI can provide highly detailed anatomical information with excellent discrimination of the soft tissues, avoiding patient's exposure to X-rays.…”
Section: Discussionmentioning
confidence: 99%